2019
DOI: 10.5888/pcd16.180634
|View full text |Cite
|
Sign up to set email alerts
|

FRESH: Long-Term Outcomes of a Randomized Trial to Reduce Radon and Tobacco Smoke in the Home

Abstract: IntroductionTobacco smoke and radon are the leading causes of lung cancer. The FRESH intervention was a randomized controlled trial of 515 homeowners to promote stage of action to reduce radon and air nicotine levels. MethodsWe studied 515 participants, 257 in a treatment group and 258 in a control group. Treatment participants received free radon and air nicotine test kits, report back, and telephone support, and those participants whose homes had high radon levels received a voucher for $600 toward mitigatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 23 publications
2
22
1
Order By: Relevance
“…Longer monitoring of testing rates will also facilitate an examination of any sustained economic benefits of the new communication strategy, as our study calculated only the NPV for a single year, not a recurring, annual value. Fourth, data on actual mitigation is not available in Kentucky; we approximated mitigation rates using estimates from a large randomized controlled trial conducted in the state [29]. Further health and economic studies are needed to more accurately approximate the rates as well as the cost of actual radon mitigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Longer monitoring of testing rates will also facilitate an examination of any sustained economic benefits of the new communication strategy, as our study calculated only the NPV for a single year, not a recurring, annual value. Fourth, data on actual mitigation is not available in Kentucky; we approximated mitigation rates using estimates from a large randomized controlled trial conducted in the state [29]. Further health and economic studies are needed to more accurately approximate the rates as well as the cost of actual radon mitigation.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 42% of Kentucky homes tested for radon contain concentrations at or above the USEPA action level of 4.0 pCi/L (Radon Policy Division: Kentucky Geologic Radon Potential Map Project, Kentucky Residential Radon Registry, unpublished). We estimated, based on the results of a randomized controlled trial in the state [29] that the percentage of these tested homes containing radon concentrations ≥4.0 pCi/L that are mitigated ranges from 17 to 22%; we used an average mitigation rate of 20% for our calculations. For this analysis, we assumed that home mitigation actions were successful in reducing radon-induced lung cancer risk to zero, all else being equal.…”
Section: Economic Benefits Estimationmentioning
confidence: 99%
“…The positive effects of app on improved knowledge suggest that delivering content in short, simple terms via a mobile app is an effective way to communicate radon-related information. The app is a very different style of content delivery than the explanations typically used in pamphlets and brochures [11,12] or in telephone interviews [9,10]. With several notable exceptions [8,12,23]e.g., an increase in radon test kit purchases reported among individuals exposed to digital signs in physicians' waiting rooms [8] few intervention studies have reported that the intervention improved individuals' knowledge, attitudes, perceptions, or behaviors.…”
Section: Summary Of Findings and Limitationsmentioning
confidence: 99%
“…Several studies have developed educational interventions concerning radon and a few have tested their effectiveness [8][9][10][11][12]. To the extent that interventions have been tested, most have performed poorly when measured against "real world" outcomes, such as increases in testing rates and home remediation.…”
Section: Introductionmentioning
confidence: 99%
“…Public health (among others) can use social media to test the effectiveness of different messages at low cost, permitting highly tailored health messaging (13). Working together, public health, health care, and other agencies can use vouchers and feedback to help achieve public health goals, such as reducing radon exposure (14).…”
mentioning
confidence: 99%